61.3k views
5 votes
SIMPLIFY THE FOLLOWING EXPRESSION: given that s ≠ 0, and write your answer using only positive exponents. Thanks in advance!!!


( {3s}^( - 4) {t}^(7) {s}^(0) )^( - 2) ( - 2 {s}^(2) {t}^(5) )^(2)


SIMPLIFY THE FOLLOWING EXPRESSION: given that s ≠ 0, and write your answer using only-example-1

1 Answer

2 votes

Answer:

4s¹²/(9t⁴)

Explanation:

Solving in steps:

  • (3s⁻⁴t⁷s⁰)⁻²(-2s²t⁵)² =
  • 3⁻²s⁻⁴ˣ⁻²t⁷ˣ⁻²(-2)²s²ˣ²t⁵ˣ² =
  • 1/9×s⁸t⁻¹⁴(4)s⁴t¹⁰ =
  • 4/9 ×s⁸⁺⁴t⁻¹⁴⁺¹⁰ =
  • 4/9 ×s¹²t⁻⁴=
  • 4s¹²/(9t⁴)
User Pablo Morales
by
4.8k points